Perceived goal setting practices across a competitive season. Issue 6 (December 2019) - Forsblom, Kim; Konttinen, Niilo; Weinberg, Robert; Matilainen, Pertti; Lintunen, Taru
Goal setting is an effective and frequently used tool for performance enhancement in sports. However, in the previous studies, the focus has been on goal effectiveness among individual male athletes and at one point in time. Therefore, the purpose of this longitudinal study was to examine goal setting practices in women's sport teams across a competitive season from players' individual and team perspectives. A total of 146 female players representing 24 teams in ice hockey, ringette, or floorball completed three online surveys. Surveys focused on setting outcome, process, and performance goals, as well as evaluating the follow-through of setting goals and actually reaching these goals across the season. The results indicated that teams set collective outcome goals, and several process, and performance goals at the outset of the season. One-third of the participants reported that these goals were recorded. Furthermore, results revealed that after the season, the achievement of the outcome goal was evaluated, whereas the attainment of process and performance goals was evaluated only occasionally. It is argued that the lack of follow-through in evaluating process and performance goals may be attributed to setting too many goals and not writing them down. It appeared that one-third of the teams did consistently follow the goal setting principles, and although this resulted in increased goal evaluation, it did not result in increased goal attainment. A number of future directions for research are offered and it is recommended that coaches should be made more aware of these guidelines and the importance of following them to achieve maximum benefits of a goal setting program.